Equality in access to public office in the Sultanate of Oman - Mohammed bin Khamis bin Hamad Al-Nofli (International Journal of Law Research and Studies, 2025)
Equality is one of fundamental principles enshrined in the constitutions of respected countries worldwide since the state plays a crucial role in organizing individual life across social, economic, and political spheres. All citizens are equal and entitled to equal employment without any discrimination based on non-objective grounds such as gender, ethnicity, political affiliation as far as the person is fit for the job. The Omani legislator upholds the equality in employment while the Basic Statue of the State the legislative provisions in the Civil Service Law and all employment regulations within the administrative units of the Administrative Apparatus of the State mandate the same principle. This study is significant because it handles one of the key issues concerning human resources given the fact that human capital is a crucial foundation for a modern state and its right to determine the fitness of jobseekers for public service employment based on the equality of job opportunities and recruitment and whether this principle is concordant with the legislative provisions that safeguard the equal entitlement of citizens to public service jobs. The title of the study of “Equal Employment in Public Service”.